Current Situation and Position of Fisheries Production of Sinop Province in Turkey’s Fisheries Production - Şennan Yücel; Birol Baki; Tuçe Altın; Gülşen Uzun Gören (Turkish Journal of Agriculture: Food Science and Technology)
In the present study, the production amount in the last five years (2015-2019) of Sinop province, which is located in the Black Sea Region and a significant part of fisheries production is carried out, was evaluated. For this purpose; Sinop Provincial Directorate of Agriculture and Forestry and TUIK (Turkish Statistical Institute) data were used. There are 2.326 commercial fishermen and 444 fishing boats in Sinop province. In the sea area of Sinop, 5 enterprises still produce culture fish in cages. The 2 potential marine culture areas identified in Sinop have an annual production capacity of 32.430 tons (31 enterprises). In addition, 5 bivalves (4.940 tons/year) and 1.000.000 number/year capacity juvenile fish production facilities are at the project stage. The total fisheries production of Sinop Province in 2019 was 34.620,9 tons, and 1.505 tons were obtained from aquaculture. In addition to these, 3.924 tons of fish processing facilities per year, and 35 tons of fish meal and oil processing facilities per year are operated. 66% of sea fish caught in Sinop are anchovy (Engraulis encrasicolus ponticus), 16% sprat (Sprattus sprattus phalericus), 13% horse mackerel (Trachurus trachurus), 3% bluefish (Pomatomus saltatrix) and 2% consists of other species. The most preferred marine fish by the consumers are anchovy (Engraulis encrasicolus ponticus), horse mackerel (Trachurus trachurus), whiting (Merlangus merlangus), red mullet (Mullus barbatus), bluefish (Pomatomus saltatrix), turbot (Psetta maxima) and bonito (Sarda sarda) and sea bream (Sparus aurata), sea bass (Dicentrarchus labrax) and rainbow trout (Oncorhyncus mykiss) are the culture fish species offered for sale throughout the year.